Barriers to effective hypertension management in rural Bihar, India: A cross-sectional, linked supply- and demand-side study. - Michael A Peters; Olakunle Alonge; Anbrasi Edward; Yvonne Commodore-Mensah; Japneet Kaur; Navneet Kumar; Krishna D Rao (Public Library of Science (PLoS), 2022)
Effective management of hypertension in low- and middle-income settings is a persistent public health challenge. This study examined supply- and demand-side barriers to receiving quality care and achieving effective hypertension management in rural Bihar, India. A state-representative household survey collected information from adults over 30 years of age on characteristics of the hypertension screening, diagnosis, and management services they received. A linked provider assessment determined the percent of providers who provided quality hypertension care (i.e., had a functioning BP measurement device, measured a patient's BP, could correctly diagnose hypertension, had at least one first-line antihypertension medication, and could prescribe correctly based on standard guidelines). Patients were linked with their provider to determine the quality-adjusted coverage of hypertension management and logistic regression analysis was conducted to determine characteristics associated with receiving quality care. A total of 14,386 patients and 390 providers were studied. Nearly a quarter (22.5%) of adults had never had their BP measured before and 8.1% of adults reported a previous hypertension diagnosis. Less than one third (31.0%) of all interviewed providers demonstrated ability to provide quality hypertension care, and quality varied between provider types (14.8% of private homeopathic, 25.2% of informal, 40.0% of private modern medicine, and 60.0% of public providers gave quality care). While 95.8% of diagnosed individuals received some treatment, only 10.9% of patients received care from quality local providers. Nearly 45% of individuals with hypertension received care from non-local providers. Individuals from the general caste with comorbidities living in villages with more high-quality providers were most likely to receive quality care from a local provider. Whereas the coverage of services for individuals diagnosed with hypertension is high, the quality of these services is suboptimal for economically and socially vulnerable populations, which limits effective management and control of hypertension in rural Bihar. Efforts should be targeted towards providers to initiate quality treatment upon diagnosis, including correct prescription of antihypertensives.